Recent Updates on Multiple Myeloma - Ahmed Al-Anazi, Khalid (IntechOpen, 2023)
This book provides a comprehensive overview of multiple myeloma. It is organized into three sections with chapters addressing topics such as diagnosis, risk stratification, and management of multiple myeloma; treatment of multiple myeloma at diagnosis and at relapse; management of disease complications; and stem cell therapies, including autologous and allogeneic hematopoietic stem cell transplantation with a focus on autologous grafting using non-cryopreserved stem cells and performance of stem cell transplantation in outpatient settings.